Efficiency and Mechanism Evaluation of Magnolia officinalis Water Extract in Preventing Gastric Ulcer. (6th April 2023) - Shen, Kuo-Ping; Chang, Ching-Dong; Hsieh, Meng-Hsun; Chaung, Hso-Chi
Abstract : In this study we aimed at demonstrating the ability of Magnolia officinalis water extract to ameliorate gastric ulcers in in vitro and in vivo experiments. The gastric mucosa epithelial cell line, RGM 1, was pretreated with Magnolia officinalis water extract (0, 0.1, 1, 2, 5, or 10 mg/ml) and cultured in DMEM/F12 medium (pH 7.4) for 2 h and then in DMEM/F12 medium (pH 4.0) for 10 min. Magnolia officinalis water extract protected the cell viability and decreased reactive oxygen species formation by the acidic medium. In the in vivo experiment, Magnolia officinalis water extract (100 mg/kg) was administrated daily for 28 days in ICR mice via oral gavage, and then Shay's ulcer surgical method was performed to induce gastric ulcers. We analyzed the pH value of stomach acid and the pathological section, inflammation, and cannabinoid receptor type 2 (CB2) cDNA levels of the stomach. Magnolia officinalis water extract not only enhanced the pH value of stomach acid but also ameliorated the ulcer index and inflammation and increased CB2 expression effectively. These results suggest that Magnolia officinalis water extract might be used to decrease the incidence of gastric ulcer.